Development of interactive software (Normal stress) - Yu, Qing (2016)
Normal stress of a beam is a critical quantity in analysis or design of a structural components. One of the common application is the maximum normal stress and the position it occurs. And it is a compulsory test content in the Mechanics of materials course. The objective of this project is to develop an interactive software that can perform simulation and analysis of normal stress in an educational purpose. It can be a teaching tool to assist professors in helping students calculating the maximum normal stress and understand the concepts and principles at the same time. The user interface is designed to be simple and clear, and easy to operate. The program was designed for students who take Mechanics of Materials, a second year course of School of Mechanics and Aerospace Engineering, Nanyang Technological University, but its usage has been broadened to anyone who need assistance in calculating maximum normal stress on a beam. The program calculates normal stress along the beam, and presents the magnitude and the position it occurs graphically. The users are able to input five kinds of reactions (point load, moment, uniformly distributed load, varying load, and non-uniformly distributed load), two kinds of supports (simple support, fixed end), and shape & dimensions of beam cross-section. The program can handle cases of any combinations of the loads & supports stated above, including statically indeterminate cases, which are seldom discussed in textbooks. The programing language used for this program is JAVA. The program is executed in explorers but it is able to perform its entire functions offline as well. Iterative and incremental development model is adopted as the development model of this program. The program is designed modularly to allow further development or improvements in the future.